Experimental and numerical analysis of the spray application on apple fruit in a bin for postharvest treatments. (June 2017) - Ambaw, A.; Dekeyser, D.; Vanwalleghem, T.; Van Hemelrijck, W.; Nuyttens, D.; Delele, M.A.; Ramon, H.; Nicolai, B.; Bylemans, D.; Opara, U.L.; Verboven, P.
Abstract: Postharvest treatment of fruit inside a cool room is gaining more interest to replace spray applications in the orchard. The efficacy of the application depends on the quality of the spray liquid and its distribution inside fruit bin. This work investigated the effect of different modes and settings of airflow delivery on the deposition amount and uniformity of the cold fogging spray deposition in a single bin. Room air circulation by means of evaporator fans was compared to an air suction configuration using a tunnel and suction fan. Deposition tests were conducted using a mineral chelate tracer solution and filter paper collectors placed on fruit. A computational fluid dynamics (CFD) model of the spraying process was developed to simulate the airflow, droplet particle tracks and spray deposits on fruits. The model predicted well the position of maximum and minimum deposit and the relative differences between the different modes and settings of airflow delivery. Generally, deposition distributions were strongly non-uniform. Spray deposits on fruit using only room air circulation were very low. Using suction airflow that directs the spray through the bin improved spray deposition and uniformity. The effects of spraying under different suction pressures (50, 167, 314 and 500 Pa) across the bin using different droplet diameters (15, 100, 200 and 300 μm) was evaluated. Depending on the size, different effects were observed. Coarse droplets perform best in terms of uniformity of deposition with more lateral dispersion, whereas fine droplets have a very limited lateral dispersion, travels deep to the stack following the high-velocity air (better axial dispersion). By implementing multiple nozzles the poor lateral dispersion of fine droplets can be improved, hence, the desirable characteristics of fine droplets in penetrating into the stack (axial distribution) can be retained. Highlights: Spraying application in postharvest was examined experimentally and mathematically. Suction pressure and droplet sizes affects droplet deposition distribution. Spraying in cool store room resulted in a very low amount of deposition. Spraying in a tunnel looks a potential alternative. Study incorporating bio-efficacy testes is recommended to choose optimal settings.